Ruang senja: edukasi dan pendampingan kesehatan mental untuk meningkatkan kesejahteraan psikologis lansia di Desa Tlompakan - Taofan Ali Achmadi; Nanda Pertiwi; Doflavio Farela Firdaus; Sunardi Sunardi; Srihatmini Srihatmini (CV Rezki Media, 2026)
Mental health issues among the elderly in Tlompakan Krajan Hamlet are often overlooked due to various changes, such as declining physical condition, reduced social roles, loss of a partner, and limited interaction with family. These conditions trigger feelings of loneliness, anxiety, and sadness that are often suppressed. The lack of sharing spaces and low mental health literacy put the elderly at risk of social isolation and a decline in overall quality of life. In response to these problems, KKN GIAT 15 UNNES, together with the Tlompakan Village Midwife, implemented the Senja Room program as a mental health education and support program for the elderly. The methods used were interactive lectures, discussions, and experience sharing, games for recognizing emotions and reflecting on gratitude, and relaxation practices using deep breathing and butterfly hug techniques. The results of the activity showed that the elderly were present and participated in all activities; participants began to dare to share their experiences in discussions; participants were able to understand and explain the importance of maintaining mental health; and most of the elderly appeared more relaxed after the relaxation session. This program helps seniors feel more valued, less alone, and motivated to stay socially and emotionally active. The Senja Room program is expected to be the first step toward building a community that cares more about seniors' psychological well-being.